Peladang (S) Fishmart Sdn Bhd : A strategic analysis / Antony Puro … [et al.]. - Puro, Antony; Lo, Eleanor; Ngisau, Noni; Sazin, Paul (2010)
The fishing industry is an important player in the socio-economy development of Malaysia and has contributed significantly to the economy. Such contributions are significant to the economy as it has linkages to many other industries such as the manufacturing and financial services industries. With the ever-changing global market in the business environment and due to the recent global economic turmoil, fishery companies need to have the competitive advantage and achieve greater efficiency to stay in the game. This research undertakes a strategic analysis of Peladang (S) Fishmart Sdn Bhd, a local aquaculture company, using the Strategy-Formulation Analytical Framework and based on the findings of this analysis, propose recommendations to further improve the company performance.